A Companion to Josephus in the Medieval West - Hilliard, Paul C.,; Kletter, Karen M., (Brill's Companions to the Christian Tradition ;, 2024)
The works of Titus Flavius Josephus ben Matthias on biblical history and the Jewish war were read and studied throughout the Latin west during the Middle Ages. Each generation of Christian scholars had to contend with the Jewish writer's text, reputation, and content. This volume demonstrates the complex relationship between Josephus' legacy and his readers who sought to make use of that legacy across the period of 500 to 1300. Contributors include: Carson Bay, Susan Edgington, Anthony Ellis, Paul C. Hilliard, Karen M. Kletter, Justin Lake, Richard M. Pollard, Graeme Ward, and Julian Yolles.